The Effectiveness of Roselle Kombucha Tea in Increasing Haemoglobin Levels Mice (Mus imusculus) With Anaemic - Tut Rayani Aksohini Wijayanti; Reny Retnaningsih (Faculty of Medicine, University of Jember, 2023)
Anaemic caused by Iron deficiency can be affected by a lack of vitamin C. Vitamin C can reduce ferrous iron (Fe3+) to ferrous (Fe2+) in the small intestine so that it is easily absorbed. Kombucha tea is a functional drink known to the public for a long time and provides health benefits. The study aimed to determine the effectiveness of kombucha rosella tea against increasing haemoglobin levels in mice (Mus musculus) anaemic. The type of research is true experimental with a pre-post test randomized control group design. Treatment with four treatments and three repetitions. The sample from this study was mice (Mus musculus), female, 2-3 months, weighing 20-25 as many as 24 heads. Administration of kombucha rosella tea in anaemic mice at different doses (0.36 ml / 20 g BB, 0.55 ml / 20 g BB and 0.73 ml / 20 g BB) for 14 days. Giving kombucha rosella tea can increase haemoglobin levels in the blood of mice (Mus musculus) anaemic. The optimal dose of use of kombucha rosella tea against an increase in haemoglobin levels in the blood of anaemic mice is 0.73 ml / 20 g BB. It is necessary to conduct further research on using kombucha rosella tea in human subjects to obtain further substantiation of the benefits of kombucha rosella tea as a treatment therapy.